The Stages of Invasion: How does a nonnative species transition to an invader? - Deah Lieurance; Amy Kendig; Christina Romagosa (EDIS, 2022)
This publication describes why invasive species are an important issue in Florida and how nonnative species become invasive by moving through five stages of human-aided biological invasion. Written by Deah Lieurance, Amy Kendig, and Christina Romagosa, and published by the UF/IFAS Agronomy Department, July 2022.